The Influence of Stress on Industrial Operator’s Physiology and Work Performance - Kamarulzaman, Mahmad Khairai; Sutarto, Auditya Purwandini; Muhammad Nubli, Abdul Wahab (Indonesian Institute of Science, Universitas Andalas, 2020)
Elevated stress has been widely associated with physical and physiological threats as well as reduced work performance. However, there is still a lack of studies that investigate whether stress influences concurrently physiological and objective work performance. The purpose of this study is to examine whether workers’ level of stress or negative emotional symptoms correlates with their physiological coherence and work performance. Eighteen female operators who reported high severity levels of stress, assessed using the Depression, Anxiety, and Stress Scale (DASS-42) were categorized as the risk group. The comparison group was formed by randomly selecting 18 of 99 female workers who had significantly lower DASS scores. Both participants attended one session of physiological measurement. Their work performance was observed by calculating their cycle time completing a product during five workdays. A significant difference in HRV between the two groups was also found in physiological and work performance measures. The results showed that workers in the risk group obtained significantly lower coherence levels and longer work cycle time than the control participants, indicating that negative emotional symptoms were parallel with physiological coherence and work performance. However, a weak correlation was found between work performance and negative emotional symptoms as well as physiological coherence. Despite the study limitations, our findings support to evidence the more complete picture of how stress affects female worker’s physiology and work performance, suggesting a need to implement effective workplace stress intervention. Further study is needed to be conducted among different group characteristics such as male and occupational settings.